Equações de referência para os testes de caminhada de campo em adultos saudáveis - Dourado, Victor Zuniga [UNIFESP] (2011)
OBJECTIVE: To develop regression equations for predicting six-minute and incremental shuttle walk distances (6MWD and ISWD, respectively), based on demographic characteristics, anthropometric variables, and grip strength. METHODS: We evaluated 6MWD and ISWD in 98 healthy adults. Height, weight, and grip strength were also assessed. Using data from 90 of the participants (40 males; 60 ± 9 years of age), we devised linear equations adjusted for age, gender, height, and weight, and we developed alternate models that included grip strength. We prospectively applied the equations in the 8 remaining participants (4 males; 59 ± 10 years), who had been randomly separated from the initial sample. RESULTS: Age, gender, height, and weight collectively explained 54.5% and 64.9% of the variance in 6MWD and ISWD, respectively, whereas age, height, weight, and grip strength collectively explained 54.4% and 69.0% of the respective variances. There was no significant difference between the measured and predicted 6MWD using equations with and without grip strength (14 ± 57 vs. 13 ± 67 m). Similar results were observed for ISWD (25 ± 104 vs. 25 ± 93 m). CONCLUSIONS: Grip strength is a determinant of ISWD and 6MWD; however, it could not improve the power of equations adjusted by demographic and anthropometric variables. The validity of our models including grip strength should be further evaluated in patients with skeletal muscle dysfunction.